Establishing Trustworthiness. Studying Leaders and Mobilisation in Two Social Movements in India - Wenner, Miriam; Lieberherr, Silva (PARTECIPAZIONE E CONFLITTO, 2022)
This paper enhances social movement studies by offering a strongly relational understanding of leader-follower relations for a better understanding of social movement mobilisation. It offers a conceptual framework around leadership styles, conflicts over roles, and normative moral values. Drawing on ethnographic fieldwork and intensive interactions with leaders and supporters of two social movements in India (the Gorkhaland movement in northern West Bengal, and the farmers' movements groups in Vidharba), we claim that especially leaders' trustworthiness is a necessary element in social movement mobilisation. We use the concept of trust work to highlight the various strategies that leaders employ to generate trust between themselves and their supporters and to analyse their outcomes of their efforts. Especially important is leaders' boundary work of establishing and transcending differences between an anticipated virtuous movement and dirty politics. Epistemologically, we propose that a relational approach is best suited to highlight the contested and dynamic nature of leader–follower relations. The generation of trust, we show, can best be understood at local and covert sites where leaders combine their commitment for movement issues with support for their prospective followers' struggles for survival.